Laws of King Alfred the Great, A.D. Cir. 890, Cap. 7 - (:unkn) unknown (My University)
Prohibited fighting in the King's Hall or drawing weapons. Violators may be put to death by the King. Violators who escape may be punished and fined according "to the nature of the outrage he has perpetrated.
Keywords: BRANDISHING